Individual differences in inflammatory and oxidative mechanisms of stress-related mood disorders - Kalinichenko, Liubov; Kornhuber, Johannes; Müller, Christian P. (Frontiers in Neuroendocrinology, 2019)
Emotional stress leads to the development of peripheral disorders and is recognized as a modifiable risk factor for psychiatric disorders, particularly depression and anxiety. However, not all individuals develop the negative consequences of emotional stress due to different stress coping strategies and resilience to stressful stimuli. In this review, we discuss individual differences in coping styles and the potential mechanisms that contribute to individual vulnerability to stress, such as parameters of the immune system and oxidative state. Initial differences in inflammatory and oxidative processes determine resistance to stress and stress-related disorders via the alteration of neurotransmitter content in the brain and biological fluids. Differences in coping styles may serve as possible predictors of resistance to stress and stress-related disorders, even before stressful conditions. The investigation of natural variabilities in stress resilience may allow the development of new methods for preventive medicine and the personalized treatment of stress-related conditions.
CRIS-Team Scopus Importer:2019-08-20
Keywords: Coping style; Cytokines; Depression; Immune system; Individual differences; Oxidative stress; Stress; Stress resistance; Translational medicine; Vulnerability